Cerebral Palsy among Children Visiting the Outpatient Department of Pediatric Orthopaedics in a Tertiary Care Centre - Ayushi Awale; Bibek Banskota; Prakash Yadav; Ganga Shakya; Ashok Kumar Banskota (Journal of Nepal Medical Association, 2023)
Introduction: Cerebral palsy is a group of neurological disorders that appear in infancy or early childhood and occur as a result of anomalies in the developing brain that impair the brain's capacity to regulate movement, maintain posture, and maintain balance. Healthcare professionals can better predict the need for the medical, rehabilitative, and support services needed by people with cerebral palsy by using accurate prevalence statistics. The aim of the study was to find out the prevalence of cerebral palsy among children visiting the Outpatient Department of Pediatric Orthopaedics in a tertiary care centre.